Comparación tipos de aclaramiento dental uso de consultorio y uso casero, revisión sistemática (2023)
Title: Comparison Types of Dental Whitening: Office Use and Home Use, Systematic Review. Authors: Rober Andrés Andrade Bossa and Sebastián Andrés Zamora Bernal, tenth semester, Universidad Antonio Nariño. Introduction: Dental whitening is a conservative clinical procedure, performed by dentists to solve aesthetic problems associated with the change of color in the teeth, which is due to multiple external and internal causes. Objective: To compare the side effects and benefits of both home and office teeth whitening. Methodology: A bibliographic review of the literature of articles that were published between 2017 and 2022 was carried out, aimed at a qualitative analysis, articles written in English, Spanish and Portuguese were taken into account, as well as studies describing external dental whitening systems in office and home, research describing internal dental whitening was excluded, an instrument for data extraction using the file technique was developed; according to Resolution 8430 of 1993 of the Ministry of Social Protection of Colombia, it is determined that this study is considered risk-free. Results: The dental whitenings of office, home use and combined in their composition present Carbamide Peroxide or Hydrogen Peroxide, its concentration depends on its presentation which can be powder / liquid, strips, personalized buckets, among others, the prolonged use of these whitenings can cause adverse effects, among which the most common is tooth sensitivity, which lasts from 2 to 3 days. Conclusion: The effectiveness of vital dental whitening depends on certain factors, such as the concentration of the whitening agent, the duration of the application, the additives and the remineralizing agents used, therefore, the higher the concentration of Carbamide Peroxide/Hydrogen Peroxide, the better results in the VITA color scale. Home and combined dental whitening cause a greater secondary effect due to the exposure time that the patient contains the material in the mouth. These effects can be reflected in burns at the mucosal level and postoperative sensitivity; on the contrary, whitening performed in the office has greater control and the contact time with the product is shorter.